Influence of Green Roofs on Urban Heat Island Mitigation in Canada - David, Benjamin (Journal of Environment, 2024)
Purpose: The purpose of this article examined influence of green roofs on urban heat island mitigation Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that Green roofs significantly reduced the urban heat island (UHI) effect by lowering surface temperatures by 15–30°C and ambient air temperatures by 2–4°C through insulation, solar reflection, and evapotranspiration. Their effectiveness depends on factors like vegetation type, coverage, and local climate. Beyond cooling, green roofs provide benefits such as improved air quality, energy savings, and enhanced urban biodiversity. Large-scale adoption can make cities more sustainable and resilient to climate change. Unique Contribution to Theory, Practice and Policy: Urban heat island (UHI) theory, ecosystem services theory & biophilia hypothesis may be used to anchor future studies on the influence of green roofs on urban heat island mitigation. Training programs for architects, engineers, and facility managers can enhance technical proficiency, ensuring that installation and upkeep practices maximize thermal performance. Policymakers can facilitate knowledge exchange through publicly accessible databases that document best practices, long-term performance outcomes, and innovative design solutions.